2014
DOI: 10.1159/000358678
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3� and Vitamin D Receptor are Involved in �-Catenin and Snail Signaling in High Glucose-Induced Epithelial-Mesenchymal Transition of Mouse Podocytes

Abstract: Background: Epithelial-mesenchymal transition (EMT) is recognized to play an important role in diabetic nephropathy (DN). Objective: To analyze the roles of glycogen synthase kinase 3β (GSK-3β), β-catenin and Snail signaling in high glucose (HG)-induced mouse podocytes EMT. Methods: Differentiated podocytes were divided into: the normal glucose group (NG: glucose 5.6mM), the HG groups (12.5HG: 12.5mM; 25HG: 25mM; and 50HG: 50mM of glucose), and the osmotic control group (NG+M: glucose 5.6mM and mannitol 44.4mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Vitamin D analogs also induce the expression of E-cadherin, promoting translocation of β-catenin from the nucleus to the cell membrane, to control cell growth and differentiation [19]. In our study, we found that VDR could be downregulated by high glucose and take part in the epithelial-epithelial-mesenchymal transition of podocyte in mice [21].…”
Section: The Effect Of Vitamin D In Cell Proliferation and Differentisupporting
confidence: 51%
“…Vitamin D analogs also induce the expression of E-cadherin, promoting translocation of β-catenin from the nucleus to the cell membrane, to control cell growth and differentiation [19]. In our study, we found that VDR could be downregulated by high glucose and take part in the epithelial-epithelial-mesenchymal transition of podocyte in mice [21].…”
Section: The Effect Of Vitamin D In Cell Proliferation and Differentisupporting
confidence: 51%
“…β‐catenin signals is recognized as one of the cell signalling pathways involved in EMT 28. Next, we suggested weather DKK3 regulated EMT in pancreatic cancer by suppressed β‐catenin signalling in hypoxic conditions.…”
Section: Resultsmentioning
confidence: 83%
“…Podocytes epithelial markers, such as nephrin and zonula occludens-1, are lost under diabetic condition, while mesenchymal cell markers, such as α-SMA and fibronectin are expressed, leading to podocyte dysfunction and proteinuria [25,26,27,28]. Recent study demonstrated that HG promoted podocyte EMT, as shown by decreased nephrin expression, and increased α-SMA expression [29]. In-vivo study further confirmed that in addition to loss of nephrin and zonula occludens-1, mesenchymal markers such as desmin, fibroblast-specific protein-1, and matrix metalloproteinase-9 could be observed in glomerular podocytes of diabetic nephropathy [21].…”
Section: Discussionmentioning
confidence: 99%